KEPEMIMPINAN VISIONER KEPALA SEKOLAH, KEPEMIMPINAN DIRI GURU DAN SEKOLAH EFEKTIF - Mappaenre, Ahmad (Jurnal Ilmu Administrasi Negara, 2014)
This study aims to determine whether the visionary leadership of principal, and selfleadership of the teachers influence the effectiveness level of the school either individually orsimultaneously. Object of this study is school, principals, and teachers at State SMK Makassar.This research uses survey research with causal quantitative approach. Research population is allprincipals and teachers (9 school, 9 principals, and 632 teachers). These 9 schools have drawnmajority sample (75 %) to obtain 7 schools and 7 principals. Sample of teachers are 103 or 21% from 489 teachers at those schools. Data was analyzed by using descriptive statistics andinferential statistics. The results showed that the visionary leadership of Chief State VocationalSchool in Makassar is good categorized (82.2 %) and self- leadership is also for the teachers(81.34 %). Both visionary leadership of the principal and teacher self leadership have an influenceon effective schools, it means only 0.598 visionary leadership of the principal and teacher selfleadership contribute effectively to the school (34.4 %). The remaining 65.6 % is determined byother factors. Key words: visionary leadership, self leadership, effective schools, agent of change.